2006
DOI: 10.1038/nature05027
|View full text |Cite
|
Sign up to set email alerts
|

Cooling a nanomechanical resonator with quantum back-action

Abstract: Surprisingly, when biasing near a transport resonance, we observe cooling of the nanomechanical mode from 550 mK to 300 mK. These measurements have implications for nanomechanical readout of quantum information devices and the limits of ultra-sensitive force microscopy, e.g. single nuclear spin magnetic resonance force microscopy. Furthermore, we anticipate the use of these backaction effects to prepare ultra-cold and quantum states of mechanical structures, which would not be accessible with existing technolo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
583
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 539 publications
(589 citation statements)
references
References 29 publications
5
583
0
1
Order By: Relevance
“…We explain the classical effects of retarded radiation forces. Similar physics was investigated in a variety of other system, like driven LC-circuits coupled to cantilevers (Brown et al, 2007) or single-electron transistors and microwave cavities coupled to nanobeams (Naik et al, 2006;D A Rodrigues and Armour, 2007;Regal et al, 2008). Light-induced forces can not only cool the cantilever, but can also enhance the mechanical motion leading to an instability.…”
Section: Introductionmentioning
confidence: 99%
“…We explain the classical effects of retarded radiation forces. Similar physics was investigated in a variety of other system, like driven LC-circuits coupled to cantilevers (Brown et al, 2007) or single-electron transistors and microwave cavities coupled to nanobeams (Naik et al, 2006;D A Rodrigues and Armour, 2007;Regal et al, 2008). Light-induced forces can not only cool the cantilever, but can also enhance the mechanical motion leading to an instability.…”
Section: Introductionmentioning
confidence: 99%
“…195 Nevertheless, achieving subattonewton sensitivity may require moving beyond single-crystal silicon oscillators. While Si 3 N 4 was initially abandoned as a material for ultrasensitive cantilevers in favor of single crystal silicon, 38 recent work has shown that large increases in Si 3 N 4 's mechanical quality factor can be realized by working at millikelvin temperature 179 or by applying strains. 196 Novel materials such as metallic glasses 197 may potentially exhibit ultralow mechanical dissipation.…”
Section: Future Directions In Mechanically Detected Magnetic Resmentioning
confidence: 99%
“…Achieving thermally limited force detection of rf cantilever motion at cryogenic temperatures is extremely challenging, but has been achieved, for example, by coupling a rf single-electron transistor to a metal-coated Si 3 N 4 cantilever 179 and by harnessing the piezoresistivity of a thin metal film coating a SiC cantilever. 180 Displacement detectors based on tunnel sensors are under development for use with rf cantilevers, 181 and one can also imagine using on-chip ring resonators to achieve exquisitely sensitive displacement sensing.…”
Section: Future Directions In Mechanically Detected Magnetic Resmentioning
confidence: 99%
“…2. 45 Due to the nature of the problem, it seems reasonable to imagine that for a narrow longitudinal (along the beam) constriction with a transverse opening, squeeze-films get evacuated much more quickly than diffusion would suggest. In fact molecules in a squeeze film execute Lévy walks [247], lending plausibility to their absence after even a short pumping time.…”
Section: Nature Of Elastic Force: Radiation Pressure Vs Thermoelastimentioning
confidence: 99%
“…nano-mechanical oscillators, featuring very high mechanical quality, brought the dream of witnessing the vacuum fluctuations of a macroscopic object ever closer. Integrating such oscillators with sensitive radio-frequency amplifiers, like single-electron transistors [43][44][45], quantum-point contacts [46,47], or SQUIDs [48], proved to be fruitful in terms of approaching the sensitivity required to see vacuum fluctuations (i.e. the standard quantum limit (SQL)).…”
Section: Precise Position Measurementsmentioning
confidence: 99%